Capital structure and its determinants in companies originating from two opposite sides of the European Union: Poland and Portugal - Czerwonka, Leszek; Jaworski, Jacek (Economics and Business Review, 2022)
The aim of the paper is to identify differences in enterprises’ capital structureand its determinants in Poland and Portugal. The research applies statistical methodsto the financial data of 22,775 Polish enterprises and 36,625 Portuguese enterprisesfor the years 2010–2017. The research results show that: (i) despite several years of ongoingeconomic integration in the EU differences in enterprises’ capital structure inold and new countries of the community still exist, (ii) in Portugal representing theold EU enterprises are more likely to use debt than in Poland being an emerging EUeconomy, (iii) in Polish enterprises, tangibility, profitability, liquidity and non-debt taxshield exert a negative impact on debt; while growth and size have a positive impact;in Portugal tangibility and a non-debt tax shield show the opposite, (iv) in both countriesindustry growth decreases indebtedness of enterprises while financial risk resultsin higher debt; in addition, in Portugal the capital intensity of industry increases theshare of debt in capital structure.